Impact of Printing Orientation on the Accuracy of Additively Fabricated Denture Base Materials: A Systematic Review - Maram A. AlGhamdi; Mohammed M. Gad (MDPI AG, 2024)
Printing orientation is one of the printing parameters that affect the properties of three-dimensional (3D)-printed resins. Different printing orientations and directions have been suggested; however, no clear and specific orientations are recommended in the literature in terms of the printing orientation effect on the accuracy and fit of 3D-printed removable dental prostheses. This review aimed to evaluate the effect of printing orientation on the fit and accuracy of 3D-printed removable dental prostheses. The PubMed, Scopus, and Web of Science databases were searched for published articles that investigated the effect of printing orientations on the accuracy and fit of the 3D-printed denture base. Full-length English published articles were searched between January 2010 and December 2023, which examined topics related to printing orientations, building angles, 3D printing, printing technology, accuracy, dimensional changes, internal fit, marginal integrity, marginal discrepancies, trueness, precision, and adaptation. Of the ten included studies, one investigated maxillary and mandibular denture bases, seven assessed maxillary denture bases, and two evaluated mandibular bases. Different printing orientations, ranging from 0° to 315°, were explored, with a higher prevalence of 0°, 45°, and 90°. The included studies utilized stereolithography and digital light processing printing technologies. High accuracy was observed at 45°, followed by 90. Additional struts and bars on the cameo surface increased the accuracy of the 3D-printed denture base. These results shows that printing orientation has a significant effect on the accuracy of 3D-printed resin, with 45° exhibiting the highest accuracy. In addition to the support structure, the density and position can impact the accuracy.